The effects of aqueous extracts of selected Philippine sponges on nile tilapia (Oreochromis niloticus) fingerlings. - Ilejay, Zinotchka Gerodias (1999.)
The study was conducted to contribute to the growing knowledge on sponge ichthyotoxicity as well as to aid in the identification of sponges that may contain metabolites of economic and biomedical importance. The purpose of the study was to test some Philippine sponges for ichthyotoxicity. It aimed to determine the lethal and sublethal effects of aqueous extracts of selected Philippine sponges on Nile Tilapia fingerlings and to establish a hierarchy of toxicity for the sponges. Three sponges were collected in Taklong Island, Guimaras. The sponge extracts were tested for their toxic and behavioral effects on fish using 48-hour ichthyotoxic test. Two were found toxic to the fish. Of these, Xestospongia exigua was the most toxic, killing 72.22 percent of the fish at 15ppm withing 24 hours. Spheciosphongia vagabunda at 15ppm cause 66.67 percent mortality after 48 hours. Sublethal effects included immediate hyperactivity from S. vagabunda extracts while X. exigua had no initial effect on the test animal. Prolonged exposure to both extracts, however, induced hypoactive swimming movements with the fish frequently settling motionless on the bottom or the surface of the water, slow reaction to unresponsiveness to visual stimulus and disorientation. These behavioral changes all denote stress and avoidance responses. Stylotella aurantium was nontoxic and did not show behavioral modifications distinguishable from the controls.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Tilapia -- Fingerlings -- Research; Oreochromis niloticus -- Research